Trends and Development of Tourism Product Diversification in Botswana: Lessons Learned - VUMBUNU, Tonderai; VIVIERS, Pierre-Andre; DU PLESSIS, Engelina (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).09, 2022)
Diversifying tourism products is a vital contemporary business strategy for maintaining a competitive advantage in the face of rapid technological, economic and social changes. Tourism in Botswana is largely dependent on wildlife and international tourists and consistent calls to diversify over the past four decades have greatly been amplified by the colossal impact of the COVID-19 pandemic. A semi-systematic literature review analyzed progress and research trends related to tourism product diversification in Botswana. Findings revealed that research on diversification is largely qualitative and supply-side focused. It mostly explains reasons for diversification and identifies potential development sites and optional products that could be introduced such as activities related to cultural, heritage and community-based tourism. Tourism product diversification has largely been stalled over the past four decades and is characterized by a deficiency in empirical demand-side research, precise strategies to adopt as well as theoretical and conceptual analyses of diversification that should form the basis for crafting time-specific effective strategies.